CIDP in elderly patients with sensory ataxia: Never forget to think about Contactin 1 spectrum - Marcus Vinícius Magno Gonçalves; André Eduardo de Almeida Franzoi; Rinaldo Claudino; Osvaldo Nascimento (Journal of Neurology, Neurological Science and Disorders - Peertechz Publications, 2019)
Chronic inflammatory demyelinating polyneuropathy (CIDP) is an acquired disorder of peripheral nerves. Paranodal axoglial junctions formed by the association of contactin-1 (CNTN1), contactin-associated protein 1 (CASPR), and neurofascin-155 (NF-115) play important functions in nerve impulse propagation along myelinated axons. As with neurofascin antibody-mediated CIDP, this condition may be responsive to B cell depletion therapy (anti-CD20 therapies) and refractory to intravenous immune globulin. CTCN1 antibody is an IgG4 subclass and pathophysiologically does not activate complement pathways. It justifies the poor response to intravenous immunoglobulin and possibly a better response to anti-CD20 therapies. We believe that CTCN1 antibodies may be useful as a clinical diagnostic and therapeutic response immunometric biomarker in elderly patients with CIDP and sensory ataxia.